Pemanfaatan Limbah Tandan Kosong Kelapa Sawit dan Kulit Jagung Manis menjadi Kertas Karton menggunakan Metode Organosolv: Utilization of Empty Fruit Bunch and Sweet Corn Husk Waste into Paperboard using the Organosolv Method - Ramayanti, Cindi; Sari, Winda Febrina; Mustain; Oktaviani, Erika Dwi; Mujiyanti, Apri (KOVALEN: Jurnal Riset Kimia, 2024)
Paper is generally made using cellulose, which comes from wood, as raw material. However, if wood is used without stopping, it will cause global temperatures to rise and depletion of wood resources. One alternative to replacing wood in paper production is to use empty fruit bunch (EFB) waste and sweet corn husks. This research aims to obtain optimum conditions from variations in the ratio of raw materials and cooking process solutions and to obtain cardboard paper quality under SNI 0123:2008. The method used in this research is raw material preparation, and the pulp-making process uses the organosolv method. From the results of this research, the characteristics of pulp and paperboard obtained under optimum conditions at a raw material ratio of 30:70% w/w with a cooking solution ratio of 30:50:20% v/v have a cellulose content of 60% w/w, a tensile index of 5 .83 kN/m, absorption capacity 2.35 gr/m2, and grammage 428.67 gr/m2. From these data, it can be concluded that cardboard paper is produced from EFB raw materials and sweet corn husks with a raw material ratio of 30:70 %w/w and a cooking solution ratio of 30:50:20 %w/w using the process organosolv has met SNI 0123:2008 standards on tensile index, absorption capacity and grammage regarding the quality requirements for paperboard.